Evaluation of Serum Levels of Zinc, Copper, Iron, and Zinc/Copper Ratio in Cutaneous Leishmaniasis - F Pourfallah; S Javadian; Z Zamani; R Saghiri; S Sadeghi; B Zarea; Sh Faiaz; F Mirkhani; N Fatemi (Tehran University of Medical Sciences, 2009)
Background: The purpose of this study was to evaluate the levels of zinc (Zn), copper (Cu), iron (Fe) and zinc/ copper ratio in the serum of patients with cutaneous leishmaniasis in Qom Province, center of Iran. Methods: Serum levels of zinc and copper were determined by flame atomic absorption spectrophotometer and serum iron concentration was measured by using an Auto Analyzer. The study group consisted of 60 patients with cutaneous leishmaniasis and the control group of 100 healthy volunteers from the same area who were not exposed to cutaneous leishmaniasis. Result: There were no statistically significant differences in age and body mass index between the two groups. Serum Zn (P< 0.001) and Fe (P< 0.05) levels were lower in patients with cutaneous leishmaniasis than the control group. We also found serum Cu concentration (P< 0.05) in the patient group was significantly higher than that of the control group. However, zinc/ copper ratio (P< 0.001) was lower in patients with cutaneous leishmaniasis than in the control group. Conclusion: Our data indicated that Zn/Cu ratio was significantly lower in patients with CL as compared to the controls. Earlier reports suggest that, this ratio imbalance could be a useful marker for immune dysfunction in leishmaniasis. There was also strong association of Zn, Cu and Fe with CL. It suggests the use of blood zinc, copper, iron concentration and the copper/zinc ratio (Zn/Cu), as a means for estimating the prognosis of CL.